Analisis Penilaian Kinerja Perusahaan Menggunakan Malcolm Baldrige Criteria for Performance Excellence (Studi Kasus pada PT. Danadipa Bertu Perkasa) - Rizki Aulia, Eliana; Minto Waluyo (Pusat Riset dan Inovasi Nasional, 2023)
PT. Danadipa Bertu Perkasa is a company operating in the construction sector. Based on observations, the company currently has not measured overall performance and only uses two criteria, namely strategic planning and process management. PT. Danadipa Bertu Perkasa has problems related to the service process or meeting targets which are always not on time, the average delay is 2 to 3 months from the initial target. This results in disrupted company finances and delayed employee salaries, which causes employee performance to decline. Therefore, the aim of this research is to analyze the results of measuring company performance using the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) method, determine the position of the company's performance level, and provide recommendations for improvement. The research results show that the company's performance position is in the Emerging Industry Leader class with a score of 674.77. It is known that in the performance of company employees the highest score is in the leadership category at 69.78%. Meanwhile, the lowest score was in the measurement, analysis and knowledge management category at 59.03%. So, companies must pay attention to managing data, information and knowledge resources, as well as how to make good use of information technology.